RELATIONSHIP OF PARENT PATTERNS AND LEARNING INTERESTS TO IPS LEARNING OUTCOMES - Qomarus Sanah, Avieta; Sumilah, Sumilah (Elementary School Teacher, 2019)
This study was aimed to (1) examine the correlation between parenting style and social studies learning outcomes; (2) examine the correlation between interest and social studies learning outcomes; (3) examine the correlation between parenting style and learning outcomes of social studies interest. This study used a correlation research design with a quantitative approach. This research used a saturated sampling technique of 130 students. The data collection technique used observation, interviews, questionaires and documents. The data collected was then analyzed using the descriptive stastistical and product moment analysis. The results showed that: (1) there was a positive correlation between parenting style and social studies learning outcomes, the interpretation of the closeness of the correlation showed that the category was sufficient at 41.5%; (2) there was a positive correlation between interest and social studies learning outcomes, the interpretation of the closeness of the correlation showed a very strong category that was equal to 81.8%; (3) there was a correlation between parenting style and learning outcomes of social studies interest, the interpretation of the closeness of the correlation showed a very strong correlation that was equal to 88.8%. From the results of the study it could be concluded that there was a positive correlation between parenting patterns and learning outcomes of social studies interest of Elementary Schools of Kartini Cluster Fourth Grade Sub-District of Gubug, Grobogan Regency the interpretation of the closeness of the correlation showed a very strong category that was equal to 81.8%; (3) there was a correlation between parenting style and learning outcomes of social studies interest, the interpretation of the closeness of the correlation showed a very strong correlation that was equal to 88.8%. From the results of the study it could be concluded that there was a positive correlation between parenting patterns and learning outcomes of social studies interest of Elementary Schools of Kartini Cluster Fourth Grade Sub-District of Gubug, Grobogan Regency the interpretation of the closeness of the correlation showed a very strong category that was equal to 81.8%; (3) there was a correlation between parenting style and learning outcomes of social studies interest, the interpretation of the closeness of the correlation showed a very strong correlation that was equal to 88.8%. From the results of the study it could be concluded that there was a positive correlation between parenting patterns and learning outcomes of social studies interest of Elementary Schools of Kartini Cluster Fourth Grade Sub-District of Gubug, Grobogan Regency.